Implementation of Mobile Network-Based Unmanned Aerial Vehicle (UAV) Telemetry for Ground Control Station (GCS) Monitoring - Maharani, Hastaria Willis; zuhrie, M. Syarieffuddien (Department of Electrical Engineering, Faculty of Engineering, Universitas Negeri Surabaya, 2023)
This research focuses on cellular network-based Unmanned Aerial Vehicle (UAV) telemetry used to monitor the Ground Control Station (GCS) in the Long Endurance Low Altitude (LELA) division of the Indonesian Flying Robot Contest (KRTI). This research aims to implement a cellular network telemetry work system which then the value of the Received Strength Signal Indicator (RSSI) on the Unmanned Aerial Vehicle (UAV) is compared during aerial and land conditions, Pixhawk and RaspberryPi3 as a microcontroller of the Unmanned Aerial Vehicle (UAV). The Received Strength Signal Indicator (RSSI) test shows the signal strength received in an aerial state as far as 500 meters and an altitude of 100 meters from the surface is -61 dBm and the Unmanned Aerial Vehicle (UAV) in the land shows the Received Strength Signal Indicator (RSSI) results of -39 dBm. (RSSI) of -39 dBm. The Received Strength Signal Indicator (RSSI) value during aerial and land conditions shows that the signal is classified as very good for receiving and sending data. The conclusion of this research is that cellular network telemetry is effectively used in a long range and is expected to facilitate sending and receiving data for all types of Unmanned Aerial Vehicles (UAV). Keywords: Unmanned Aerial Vehicle (UAV), Received Strength Signal Indicator (RSSI), Ground Control Station (GCS), Telemetry.